Trends and Factors Influencing Surgical Choices for Femoral Neck Fractures - Hadar Gan-Or; David Maman; Assil Mahamid; Binyamin Finkel; Loai Ahmad Takrori; Eyal Behrbalk; Yaron Berkovich (Surgical Techniques Development, 2024)
Introduction: Femoral neck fractures pose significant health risks, particularly in the elderly population, leading to mortality, morbidity, and decreased quality of life. Surgery is the preferred treatment to restore function and alleviate pain, with options including total hip arthroplasty (THA) and hemiarthroplasty (HA). However, clinical guidelines for selecting surgical procedures remain heterogeneous, prompting the need for further investigation into treatment trends and influencing factors. Methods: Data from the NIS database spanning 2016–2019 were analyzed, focusing on patients diagnosed with intracapsular femoral neck fractures and undergoing THA or HA as primary in-hospital surgeries. Advanced statistical analyses using SPSS and MATLAB were conducted to identify trends and factors influencing surgical choices. Results: Comorbidity profiles varied significantly between HA and THA patients, with specific conditions such as Alzheimer’s disease showing higher prevalence in HA patients. Demographic differences included a higher proportion of females and Medicare-insured individuals in the HA group. Racial disparities were observed, with differences in surgical preferences among various ethnic groups. THA adoption gradually increased over the study period, indicating a shift in surgical priorities. Additionally, THA patients tended to be younger on average compared with HA patients. Conclusions: This study highlights evolving trends in surgical management for femoral neck fractures and identifies factors influencing treatment decisions in our cohort. Understanding these trends and disparities is crucial for optimizing patient care and informing future clinical guidelines. Further research should focus on assessing different surgical approaches’ long-term outcomes and cost-effectiveness.